2022
DOI: 10.1111/prd.12453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of epigenetics on periodontitis and peri‐implantitis pathogenesis

Abstract: Periodontitis is a disease characterized by tooth‐associated microbial biofilms that drive chronic inflammation and destruction of periodontal‐supporting tissues. In some individuals, disease progression can lead to tooth loss. A similar condition can occur around dental implants in the form of peri‐implantitis. The immune response to bacterial challenges is not only influenced by genetic factors, but also by environmental factors. Epigenetics involves the study of gene function independent of changes to the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 127 publications
0
27
0
Order By: Relevance
“…The immune response to bacterial challenges is not only influenced by genetic factors but also by environmental factors 10 . Epigenetics involves the study of gene function independent of changes to the DNA sequence and its associated proteins, and represents a critical link between genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune response to bacterial challenges is not only influenced by genetic factors but also by environmental factors 10 . Epigenetics involves the study of gene function independent of changes to the DNA sequence and its associated proteins, and represents a critical link between genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The immune response to bacterial challenges is not only influenced by genetic factors but also by environmental factors. 10 Epigenetics involves the study of gene function independent of changes to the DNA sequence and its associated proteins, and represents a critical link between genetic and environmental factors. Epigenetic modifications have been shown to contribute to the progression of several diseases, including chronic inflammatory diseases like periodontitis and peri‐implantitis.…”
Section: Introductionmentioning
confidence: 99%
“…It does not modify the DNA sequence, but can regulate how genes are expressed, including DNA methylation, histone modification, chromatin remodeling, non-coding RNA editing and other gene regulation methods. The dysregulation of any link will affect the abnormality of chromatin structure and gene expression, which will lead to the occurrence of diseases ( 24 , 25 ). In recent years, studies have found that epigenetic modification plays an important role in the occurrence and development of cardiovascular diseases, and many epigenetic changes are reversible, which provides an optimistic prospect for disease treatment ( 26 , 27 ).…”
Section: Epigenetic Modification and Endothelial-mesenchymal Transitionmentioning
confidence: 99%
“…Periodontitis is a multifactorial disease which is born from an alteration of the balance between host, environment, and immune system [ 1 ]. The progression of the lesion is certainly mediated by the attack of bacteria that colonise the tooth surface, the gingival margin, and the subgingival environment in a susceptible host [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%